2008
DOI: 10.1002/jssc.200800044
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation of kavain on Chiralpak IA under normal‐phase, polar organic and reversed‐phase conditions

Abstract: First baseline HPLC enantioseparation of kavain is described. Complete enantiodiscrimination was achieved on the immobilised-type Chiralpak IA chiral stationary phase (CSP) using pure methanol and simple methanol-water and ethanol-water mixtures as eluents. A water-dependent enantioselectivity was clearly demonstrated. Performance of the Chiralpak IA CSP in polar organic and RP conditions was compared with that of five coated polysaccharide-derived CSPs used in normal-phase mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Thus, in the first step of this study, the enantioseparability of the selected bipyridines on Chiralpak IA and Chiralpak IC was tested under the same elution conditions (Table ) and a comparison between the behaviors of the two immobilized columns was made. In particular, Chiralpak IA is the immobilized version of Chiralpak AD‐H, so we were interested to verify the performance of the immobilized column compared to the coated one . In fact, under the same chromatographic conditions, the enantioselectivity of the immobilized CSPs can change compared to the coated CSPs: higher selectivity values can sometimes be achieved on the immobilized CSPs but, in other cases, the enantioselectivity tends to decrease .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in the first step of this study, the enantioseparability of the selected bipyridines on Chiralpak IA and Chiralpak IC was tested under the same elution conditions (Table ) and a comparison between the behaviors of the two immobilized columns was made. In particular, Chiralpak IA is the immobilized version of Chiralpak AD‐H, so we were interested to verify the performance of the immobilized column compared to the coated one . In fact, under the same chromatographic conditions, the enantioselectivity of the immobilized CSPs can change compared to the coated CSPs: higher selectivity values can sometimes be achieved on the immobilized CSPs but, in other cases, the enantioselectivity tends to decrease .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, different solvents can alter the steric structure of the polymer backbone and the binding sites inside the chiral groove, providing different selectivity on the same CSPs. For this reason, the multimodal approach is of great usefulness for method development on polysaccharide‐based CSPs because it expands the applicability of these phases for chiral separation .…”
Section: Introductionmentioning
confidence: 99%
“…In 1998 Prof. Maria Camilla Bergonzi joined the group in order to start her PhD and during the following years, first as a post-doc and since 2005 as an aggregate professor, she has strongly supported my research. Authentication, quality control and stability testing have largely been performed using not only conventional [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Our publications represented the first studies on the stability and compatibility with excipients of important dried commercial extracts, such as St. John's wort (SJW), and results were dramatic when the studies were carried out using ICH guidelines [56]. Other studies reported on the quality and/or stability of decoctions, teas and infusions, aromatic waters, tinctures and mother tinctures, commercial instant teas of common herbal drugs and obtained important information about their preparation, content and shelf-lives.…”
Section: S Telephium (Crassulaceae) (mentioning
confidence: 99%